Feedback Seeking Practices of Agricultural Extension Agents in West Java, Indonesia - Darmawiredja, Mei Rochjat; Hassan, Md Salleh; Md. Sail, Rahim; Tajuddin Shah, Raja Ahmad (Universiti Putra Malaysia Press, 1996)
Feedback seeking practices of agricultural extension agents are important for the effectiveness of research and extension programmes; This study to determine the relationship of feedback seeking practices of agricultural extension agents in West Java with some selected factors namely communication, attitude, and organisation related factors. The results revealed that communication, attitude, and organisation related factors were associated with the extension agents' feedback seeking practices. The communication and organisation related factors were found to be better predictors of the feedback seeking practices among extension agents as compared to attitude-related factors.